Copper Cobalt Sulfide Nanosheets Realizing a Promising Electrocatalytic Oxygen Evolution Reaction - Chauhan, Meenakshi; Reddy, Kasala Prabhakar; Gopinath, Chinnakonda S.; Deka, Sasanka (ACS Catalysis, 2017)
Nanostructured CuCo2S4, a mixed metal thiospinel, is found to be a benchmark electrocatalyst for oxygen evolution reaction (OER) in this study with a low overpotential, a low Tafel slope, a high durability, and a high turnover frequency (TOF) at lower mass loadings. Nanosheets of CuCo2S4 are realized from a hydrothermal synthesis method in which the average thickness of the sheets is found to be in the range of 815 nm. Aggregated nanosheets form a highly open hierarchical structure. When used as an electrocatalyst, CuCo2S4 nanosheets offer an overpotential value of 310 mV at a 10 mA cm(2) current density, which remains consistent for 10000 measured cycles in a 1 M KOH electrolyte. A chronoamperometric study reveals constant oxygen evolution for 12 h at a 10 mV s(-1) scan rate without any degradation of the activity. Furthermore, the calculated mass activity of the CuCo2S4 electrocatalyst is found to be 14.29 A/g and to afford a TOF value of 0.1431 s(-1) at 310 mV at a mass loading of 0.7 mg cm(-2). For comparison, nanostructures of Co3S4 and Cu0.5Co2.5S4 have been synthesized using a similar method followed for CuCo2S4. When compared to the OER activities among these three thiospinels and standard IrO2, CuCo2S4 nanosheets offered the highest OER activities at the same mass loading (0.7 mg/cm(-2)). Extensive X-ray photoelectron spectroscopy and electron paramagnetic resonance analyses for a mechanistic study reveal that introduction of Cu into the Co3S4 lattice enhances the oxygen evolution and kinetics by offering Cu2+ sites for utilitarian adsorption of OH, O, and OOH reactive species and also by offering a highly active high-spin state of octahedral Co3+ for OER catalysis.
Keywords: Bifunctional Electrocatalyst; Catalyst; Cuco2s4; Efficient Electrocatalyst; electrocatalyst; Electronic-structure; Nanoparticles; Nanosheet; oxide; oxygen evolution; performance; Recent Progress; Water oxidation; Water Splitting Hydrogen Evolution

Enhanced oxygen electrocatalysis in zinc-air batteries via a bifunctional bimetallic organic framework - Shivade, Rajkiran D.; Pandey, Priyanshi; Shelke, Manjusha V. (Journal of Power Sources, 2025)
An efficient bifunctional oxygen electrocatalyst, a nickel-iron metal organic framework (NF-MOF) grown within three-dimensional (3D) nitrogen doped porous carbon (NPC) collectively referred as NF-MOF@NPC, is developed as high performance electrocatalyst for oxygen reduction reaction (ORR) and oxygen evolution reaction (OER). The synergistic effect of bimetallic active sites coupled with conductive nitrogen doped porous carbon matrix, provides chemical stability, abundant active sites, enhanced electron transfer, and improve catalytic activity. NFMOF@NPC exhibits OER onset potential of 1.60 V at current density of 10 mA cm- 2 with Tafel slope of 126 mV dec- 1 and ORR half wave potential of 0.81 V with electron transfer number of 3.91. A zinc-air battery fabricated using NF-MOF@NPC shows peak power density of 102 mW cm-2 and specific capacity of 741 mAh g-Z 1n. It also exhibits remarkable cycling stability for 120 h at current density of 10 mA cm- 2 highlighting its promise as alternative for conventional platinum on carbon (Pt/C) and ruthenium dioxide (RuO2) electrocatalysts demonstrating its potential for next generation energy storage devices.
Keywords: Bifunctional Electrocatalyst; Rotating disk electrode; zinc-air battery

Highly active and durable MNS bifunctional electrocatalysts for enhanced anion exchange membrane water electrolysis - Singh, Kailash; Yadav, Himanshu; Samdani, Kunda; Selvaraj, Kaliaperumal (Electrochimica Acta, 2025)
The development of non-platinum group metal (non-PGM) electrocatalysts with performance comparable to their noble metal counterparts remains a significant challenge for overall water splitting. In this study, we demonstrate the performance of an Anion Exchange Membrane (AEM) water electrolyzer using a bifunctional, non-PGM electrocatalyst: reduced graphene oxide (rGO)-encapsulated MoS2/Ni3S2 (MNS) grown on a nickel foam (NF) substrate. The rGO/MoS2/Ni3S2 (rGO-MNS) electrode was synthesized via a facile, single-step hydrothermal method. For the hydrogen evolution reaction (HER), the rGO-MNS electrode exhibited a low overpotential of 94 mV at a current density of 100 mA cm-2, maintaining excellent stability over 50 h with a minimal degradation rate of 120 mu V h-1. In the case of the oxygen evolution reaction (OER), an overpotential of 410 mV was required to reach the same current density, with a similarly robust durability and a degradation rate of only 360 mu V h-1. When employed as symmetric electrodes for overall water electrolysis, the rGO-MNS system achieved a current density of 10 mA cm-2 at a cell voltage of 1.51 V, outperforming the benchmark Pt/C & Vert;Ru/C catalyst pair, which required 1.58 V to reach the same performance. The enhanced electrocatalytic activity and durability are attributed to the conductive rGO encapsulation, which facilitates charge transfer and mitigates surface oxidation of the catalyst. These results present a promising strategy for designing cost-effective, durable, and highperformance non-PGM electrodes for AEM water electrolysis.
Keywords: Anion Exchange Membrane Water Electrolysis; Bifunctional Electrocatalyst; hydrogen evolution reaction; Oxygen Evolution Reaction; rGO-MNS

Hydrogel electrolyte-mediated in situ Zn-anode modification and the Ru-RuO2/NGr-coated cathode for high-performance solid-state rechargeable Zn-air batteries - Kharabe, Geeta Pandurang; Verma, Tushar; Barik, Sidharth; Urkude, Rajashri R.; Ayasha, Nadeema; Ghosh, Biplab; Krishnamurty, Sailaja; Kurungot, Sreekumar (ACS Applied Materials & Interfaces, 2025)
This work aims to deal with the challenges associated with designing complementary bifunctional electrocatalysts and a separator/membrane that enables rechargeable zinc-air batteries (RZABs) with nearly solid-state operability. This solid-state RZAB was accomplished by integrating a bifunctional electrocatalyst based on Ru-RuO2 interface nanoparticles supported on nitrogen-doped (N-doped) graphene (Ru-RuO2/NGr) and a dual-doped poly(acrylic acid) hydrogel (d-PAA) electrolyte soaked in KOH with sodium stannate additive. The catalyst shows enhanced activity and stability toward the two oxygen reactions, i.e., oxygen reduction and evolution reactions (ORR and OER), with a very low potential difference (Delta E) of 0.64 V. The computational insights bring out the electronic factors contributing to the enhanced catalytic activity of Ru-RuO2/NGr based on the charge density difference (CDD) between the interfaces. The disadvantages of the existing solid-state RZABs, such as their limited lifespan brought on by passivation, dendritic growth, corrosion, and shape change, have also been taken into account. The introduction of the stannate additive to the electrolyte induced an in situ Zn-anode modification, which subsequently improved the interfacial stability of the ZABs and, hence, the battery life cycles. The experimental observations reveal that, during the charging process, the Sn nanoparticles enable the homogeneous Zn deposition on the surface of the anode. Thus, the in situ Zn-anode surface modification assisted in achieving a high-rate cycle capability, viz., the homemade catalyst-based system exhibited continuous charge-discharge cycles for 20 h at a current density of 2.0 mA cm-2, with each cycle lasting for 5 min.
Keywords: Bifunctional Electrocatalyst; Core-ShellStructure; DFT study; electrolyte additive; Hydrogel; solid-state rechargeable zinc-airbattery; X-ray absorption spectroscopy